1998
DOI: 10.1073/pnas.95.11.6355
|View full text |Cite
|
Sign up to set email alerts
|

CYR61, a product of a growth factor-inducible immediate early gene, promotes angiogenesis and tumor growth

Abstract: CYR61 is a secreted, cysteine-rich, heparinbinding protein encoded by a growth factor-inducible immediate-early gene. Acting as an extracellular, matrix-associated signaling molecule, CYR61 promotes the adhesion of endothelial cells through interaction with the integrin ␣ V ␤ 3 and augments growth factor-induced DNA synthesis in the same cell type. In this study, we show that purified CYR61 stimulates directed migration of human microvascular endothelial cells in culture through an ␣ V ␤ 3 -dependent pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
446
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(466 citation statements)
references
References 44 publications
16
446
1
3
Order By: Relevance
“…CCN1 binding to integrins stimulates cellular signaling pathways that have been shown to participate in cell proliferation [29]. Furthermore, CCN1 is known to be pro-angiogenic [30], and thus S1P may affect tumor angiogenesis through CCN1 induction. Thus, further studies will explore in more detail the roles played by CCN1 in S1P regulation of glioma cell behavior, as well other mechanisms involved in S1P regulation of glioma cell interaction with extracellular matrix, proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…CCN1 binding to integrins stimulates cellular signaling pathways that have been shown to participate in cell proliferation [29]. Furthermore, CCN1 is known to be pro-angiogenic [30], and thus S1P may affect tumor angiogenesis through CCN1 induction. Thus, further studies will explore in more detail the roles played by CCN1 in S1P regulation of glioma cell behavior, as well other mechanisms involved in S1P regulation of glioma cell interaction with extracellular matrix, proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…49 These genes are critical for neovessel formation by the stimulation of directed migration of human microvascular ECs through an ␣v␤3 integrin-dependent pathway. 50,51 In contrast, little or no induction of MMPs or TIMPs was detected up to 4 hours following PH. Other studies, however, showed overexpression of specific MMPs at later time points.…”
Section: Liver Regeneration: a Model For Hepatic Angiogenesismentioning
confidence: 94%
“…CCN1 also regulates more complex processes such as angiogenesis and tumorigenesis (Planque and Perbal 2003;Babic et al 1998Babic et al , 1999Xie et al 2001a;Tsai et al 2002). Expression of CCN1 is sufficient for acquisition of hormone independence and anti-estrogen resistance in human breast cancer cells (Tsai et al 2002).…”
Section: Introductionmentioning
confidence: 99%